Mid-Term evaluation of BRAC-Char Development and Settlement Project (CDSP)-III: Livelihoods of coastal char dwellers - Barua, Proloy (BRAC Research and Evaluation Division, 2022)
This study was undertaken to explore the socioeconomic status of coastal char (polder) dwellers as a benchmark estimate for the BRAC-CDSP-III (Char Development and Settlement Project). A survey was carried out on 795 households in July 2007 for this purpose. It investigated household demography, education, income and assets as key livelihood indicators of the char dwellers. Apart from this, the study tried to identify the factors affecting the well-being of char households. I found that 78% of the respondents were poor. The disparity was observed between poor and non-poor in terms of different livelihood indicators. The study considered per capita annual income as a proxy of household well-being that greatly influenced by household demography especially age of head, member to earner ratio, number of adult male and productive assets. Water and Sanitation (WATSAN), education and Human Rights and Legal Education (HRLE) drew serious attention of pertinent authorities, as an outreach of these services were found to be at a sub-optimal level.